Pengetahuan Pasien dan Rasionalitas Swamedikasi di Tiga Apotek Kota Panyabungan - Nur Aini Harahap; Khairunnisa Khairunnisa; Juanita Tanuwijaya (Jurnal Sains Farmasi & Klinis, 2017)
Self-medication is a part of community effort to preserve their health. In practice, the self-medication can be a source of drug related problem because of lack of knowledge about drugs and their use. The aim of this study was to determine the level of knowledge and rationality of medicinal use self-medication. This study was using survey cross-sectional method. Total respondents (n=342) were involved this study of three pharmacies. Respondents were 18-60 years old and selected by consecutive sampling method. Data was collected by using a validated questionnaire. Data were analyzed by Chi-square test and Fisher test using Statistical Product and Servicer Solution (SPSS) version 17. The research showed that level knowledge of patients 20.5 % were good, 41.8% were medium, and 37.7% were low. Drug use self-medication was 59.4% rational and 40.6% irrational used. Based the result of Chi-square and Fisher test, educated and jobs can influence the level of knowledge, meanwhile rationality of self-medication use was not influenced by sociodemographic factor. Based on the research results obtained that majority level knowledge of patient was good classified. Irrational drug use on self medication reached 40.6%.